2018
DOI: 10.1021/acs.nanolett.8b00194
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh Damping Capacities in Lightweight Structural Materials

Abstract: The demand to outperform current technologies pushes scientists to develop novel strategies, which enable the fabrication of materials with exceptional properties. Along this line, lightweight structural materials are of great interest due to their versatile applicability as sensors, catalysts, battery electrodes, and acoustic or mechanical dampers. Here, we report a strategy to design ultralight (ρ = 3 mg/cm) and hierarchically structured ceramic scaffolds of macroscopic size. Such scaffolds exhibit mechanica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…(C) Reproduced with permission. [ 71 ] Copyright 2018, American Chemical Society. (D) Reproduced with permission.…”
Section: Recent Trends In Freeze‐casting Materialsmentioning
confidence: 99%
See 4 more Smart Citations
“…(C) Reproduced with permission. [ 71 ] Copyright 2018, American Chemical Society. (D) Reproduced with permission.…”
Section: Recent Trends In Freeze‐casting Materialsmentioning
confidence: 99%
“…As another example of this, Knöller et al reported the ice‐templated fabrication of a ceramic‐based scaffold comprising V 2 O 5 nanofibers, mimicking the structure of cuttlebone, with good compressive properties at very low densities. [ 9a,71 ] Due to their very high void ratio, CNFA heterostructures, when infiltrated with water, can form unusual hydrogels. A CNFA structure formed by alginate bonded SiO 2 nanofibers was in recent work used to produce hydrogel materials accommodating high elastic deformations with strain sensitive conductivity.…”
Section: Recent Trends In Freeze‐casting Materialsmentioning
confidence: 99%
See 3 more Smart Citations